1996
DOI: 10.4065/71.12.1182
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine in the Treatment of Dermatologic Disease: An Update

Abstract: Treatment with cyclosporine is beneficial for many dermatologic diseases such as psoriasis, lichen planus, Behçet disease, atopic dermatitis, pyoderma gangrenosum, and epidermolysis bullosa acquisita. The selective action of cyclosporine on helper T cells and its rapid therapeutic action and weak myelotoxicity are the key advantages in the treatment of many dermatologic diseases. Nevertheless, drug toxicity, especially nephrotoxicity, high rates of relapse after treatment cessation, and high cost have limited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 73 publications
0
61
0
1
Order By: Relevance
“…Recent evidence implicates aberrant activation of the immune system and T lymphocyte localization in skin as critical components in the pathogenesis of psoriasis (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14), but the etiologic defect(s) in this disease remain elusive. A role for upregulated expression of autocrine regulatory networks in the pathogenesis of psoriasis has emerged from previous investigations that have suggested that epidermal hyperplasia and aberrant differentiation may result from dysregulation of the epidermal keratinocyte EGF receptor-ligand system (26, 31-35, 38, 39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence implicates aberrant activation of the immune system and T lymphocyte localization in skin as critical components in the pathogenesis of psoriasis (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14), but the etiologic defect(s) in this disease remain elusive. A role for upregulated expression of autocrine regulatory networks in the pathogenesis of psoriasis has emerged from previous investigations that have suggested that epidermal hyperplasia and aberrant differentiation may result from dysregulation of the epidermal keratinocyte EGF receptor-ligand system (26, 31-35, 38, 39).…”
Section: Discussionmentioning
confidence: 99%
“…Although the etiology of psoriasis has not been elucidated, the development of psoriatic skin lesions has been shown to be associated with infiltration of cells from the immune system, including T lymphocytes, macrophages, and neutrophils. The aberrant activity of activated T lymphocytes is thought to be paramount in the pathogenesis of psoriasis, as immunosuppressive agents such as methotrexate, cyclosporine, tacrolimus, IL-2 receptor-targeted toxins, and corticosteroids are efficacious for this disease (1)(2)(3)(4)(5)(6). Furthermore, activated CD4-positive T lymphocytes from patients with psoriasis have been shown to initiate psoriatic lesion formation in uninvolved human psoriatic skin grafted onto SCID/SCID (severe combined immunodeficient) 1 (7,8), and SCID/SCID mice reconstituted with naive CD4-positive T lymphocytes possessing a minor histocompatibility mismatch have been reported recently to initiate a psoriatic-like cutaneous reaction (9).…”
Section: Introductionmentioning
confidence: 99%
“…Pre-and post-therapy biopsies have revealed decreased T cell infiltrate and reduced expression of ICAM -1 and HLA -DRafter topical cyclosporin (36). Topical cyclosporin therapy may be more effective in oral lichen planus than in cutaneous lichen planus because of the relatively higher absorption through mucous membranes (29).…”
Section: Dermatologic Indications For Topical Immunosuppressivementioning
confidence: 99%
“…Behcet Disease -Cyclosporin is effective in controlling the ocular complications and mucocutaneous and musculoskeletal manifestations of Behcet disease (29). Ergun et al (30), reported beneficial results with topical cyclosporin in treating oral ulcers of Behcet's disease.…”
Section: Dermatologic Indications For Topical Immunosuppressivementioning
confidence: 99%
“…It is extensively biotransformed to approximately 15 metabolites, which are almost completely eliminated via the biliary system. Less than 3% of the parent compound is excreted in urine and thus higher blood levels of CsA do not occur in patients with renal dysfunction (Lim et al, 1996). CsA plasma levels peak in 2 to 4 hours and the serum half life ranges from 6.3 hours to 20.4 hours.…”
Section: Pharmacokineticsmentioning
confidence: 99%